DYNAMICS OF CLINICAL-FUNCTIONAL PARAMETERS IN PATIENTS WITH STABLE CORONARY HEART DISEASE AFTER THE REVASCULARIZATION TAKING INTO ACCOUNT THE PROGRAMS OF RESTORATIVE TREATMENT - Nesterak, R.V.; Vakaliuk, I.P.; Hryhoryshyn, R.S.; Sovtus, V.I.; Partsey, O.S.; Hrynevych, R.Y.; Veretyk, U.I. (World of Medicine and Biology, 2021)
Restorative treatment of patients with stable coronary heart disease is an important component of a comprehensive approach after the revascularization procedures. Our studies performed have shown that the dynamics of clinical-functional parameters in such patients depend on the applied programs of the restorative treatment. The use of standard therapy and restorative treatment programs has improved the quality of life by increasing physical activity, reducing angina pectoris attacks, increasing the treatment satisfaction and attitude towards illness. The developed author’s program of “Clinical-psychological rehabilitation of cardiologic patients by optimization of the internal picture of health” in combination with standard treatment and suggestive therapy, has contributed to the positive dynamics of clinical, functional, psychological components and positive impact on the long-term consequences of the disease course.
Keywords: coronary intervention; suggestive therapy; picture of health; rehabilitation